Conservação pós-colheita de melões inteiros e minimamente processados - Morgado, Cristiane Maria Ascari [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This work aimed to determine the influence of refrigeration and controlled atmosphere on quality and postharvest conservation of whole and minimally processed net melons ‘Louis’. Furthermore, the effect of heat treatment associated with the use of active modified atmosphere was evaluated in the conservation of ‘Charentais’ melons minimally processed. In the first experiment, ‘Louis’ melons were stored at 3 °C, 6 ºC, 9 ºC and 22 ºC, 80% RH, to establish the best storage temperature. In the second experiment, the fruits were stored at 6 °C (80% RH) under controlled atmosphere in concentrations of 2%, 7%, 12% and 21% O2, to determine the appropriate concentration of O2 for their conservation. In the third experiment, the melons were stored in controlled atmosphere with 5%, 10%, 15% and 20% CO2 combined with 2% O2, at 6 ºC and 80% RH. In the fourth experiment, the melons were stored under controlled atmosphere (2% O2 and 20% CO2), 6 ºC. The minimal processing was made twice, the first being the fruit immediately upon arrival to the laboratory and the second after 14 days of storage under controlled atmosphere. The fruits and minimally processed products were analyzed for color and firmness, soluble solids and titratable acidity content, pectin (soluble and total), sugars (soluble and reducers), as well as the activity of enzymes peroxidase (POD), polyphenoloxidase (PPO), polygalacturonase (PG) and pectinmethylesterase (PME). They were also analyzed as fresh weight loss, respiratory activity (2nd and 4th experiments) and sensory analysis (experiment 4). In the fifth experiment whole ‘Charentais’ melons were immersed in hot water (50 ºC for 30 min) before being subjected to minimal processing. The cubes were submitted under active modified atmosphere (2-3% O2 and 7-8% CO2), packed with oriented polypropylene film (OPP) or polylactic acid film (PLA) and stored at 6 ºC for ...

Este trabalho teve por objetivo determinar a influência da refrigeração e da atmosfera controlada na qualidade e na conservação pós-colheita de melões rendilhados do híbrido Louis inteiros e minimamente processados. Além disso, avaliou-se o efeito do tratamento térmico associado à atmosfera modificada ativa na conservação de melões tipo Charentais minimamente processados. No primeiro experimento, melões ‘Louis’ no estádio de maturação fisiológica foram armazenados a 3 ºC; 6 ºC; 9 ºC e 22 ºC, com 80% UR, para estabelecer a melhor temperatura de conservação. No segundo experimento, os frutos no estádio de maturação fisiológica foram armazenados a 6 ºC (80% UR) sob atmosfera controlada contendo 2%, 7%, 12% e 21% de O2, para estabelecer a concentração adequada de O2 para a melhor conservação da qualidade de melões ‘Louis’. No terceiro experimento, os melões também foram colhidos no estádio de maturação fisiológica e armazenados em atmosferas controladas contendo 5%, 10%, 15% e 20% de CO2 combinadas com 2% O2, na condição de 6 ºC e 80% UR. No quarto experimento, os melões foram armazenados sob atmosfera controlada (2% de O2 e 20% de CO2), a 6 ºC. O processamento mínimo foi realizado duas vezes, sendo a primeira imediatamente à chegada dos frutos ao laboratório e a segunda após 14 dias de armazenamento sob atmosfera controlada. Os frutos e os produtos minimamente processados foram analisados quanto à coloração e firmeza, teores de sólidos solúveis, de acidez titulável, pectinas (solúvel e total) e carboidratos (solúveis e redutores), bem como quanto a atividade das enzimas peroxidase (POD), polifenoloxidase (PPO), poligalacturonase (PG) e pectinametilesterase (PME). Eles também foram avaliados quanto a perda de massa fresca, atividade respiratória (2º, e 4º experimentos) e análise sensorial (4º experimento). No quinto experimento ...
Keywords: Melão; Refrigeração; Frutas - Conservação; Atmosfera; Temperatura; Melons